Augmented reality education system - Hasan, Md. Mehedi; Faiyaz, Intisar Hasnain; Bhuiyan, Ashikuzzaman; Joy, Sheakh Fahim Ahmmed (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.